The impact of student psychological empowerment on class stickiness - Fei, Hongping; Zhang, Junhui; Xiang, Weilin; Qi, Haifeng (Frontiers in Psychology, 2025)
IntroductionSustaining student engagement (“class stickiness”) in hybrid/online courses is essential for learning and retention. Grounded in customer-engagement theory, we test a sequential model where student psychological empowerment fosters psychological ownership and involvement, which in turn drive class stickiness and course evaluation.MethodsA cross-sectional survey was administered to 320 Chinese undergraduates in blended courses. Validated scales measured empowerment (10 items), ownership (10), involvement (7), stickiness (10), and evaluation (2). After Harman’s single-factor and CFA tests, structural equation modeling (LISREL 8.8) tested six hypotheses.ResultsAll scales showed high reliability (α ≥ .82) and convergent validity (AVE > .50, CR > .70). Empowerment positively predicted stickiness (β = .73, p < .001) and ownership (β = .74, p < .001). Involvement predicted stickiness (β = .90, p < .001) and ownership (β = .95, p < .001). Ownership strongly influenced stickiness (β = .95, p < .001). Stickiness enhanced course evaluation (β = .87, p < .001), explaining 76 % of its variance.DiscussionResults support the empowerment → ownership/involvement → stickiness → evaluation chain, highlighting the need for autonomy-supportive, ownership-fostering pedagogies to sustain engagement and positive course ratings in digital learning environments.